Hydrolysis of Soybean Protein by Aspergillus sojae, A. oryzae, and Rhizpus oligosporus - Endang Sutriswati Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1991)
Three species of molds, i.e. Aspergillus sojae. A. oryzae and Rhizopus oligosporus were used to hydrolyze soybean proteins. Whole soybeans were soaked overnight and cooked in boiling water for an hour, drained, sterilized at 121°C for 15 minutes, then cooled and inoculated with A. oryzae. A. sojae, and R. oligosporus. As a control treatment another batch of soybeans was prepared for spontaneous fermentation. Fermentation tasted for five days. Based on the colony forming units (CFU), A. sojae, A. oryzae R. orgosporus and the control reached the stationary phase on the third day of fermentation. The CFU of A. sojae and A. oryzae were higher than that of the others, with 107 - 108 CFU/g dry weight for A. sojae and A oryzae and 106 - 107 CFU/g dry weight for the others. The proteolytic activity of A. sojae. oryzae, R. oboosporus and the control was maximum on the third day. The proteolytic activity of A: sojae and A. oryzae using soybean as substrate was higher (180 - 200 units tyrosine/g dry weight) than the other two groups (100 - 120 UT/g dry weight).Based on the efficiency of hydrolysis, A. sojae and A. oryzae had a higher hydrolysis percentage, giving 32 - 33% and total soluble nitrogen of 2.1 - 2.2 percent/g dry weight. The hydrolysis efficiency of R. ologosporus and the control was 21 - 22%. with the total soluble nitrogen 1.4 - 1.5 percent/g dry weight. The difference in initial pH i.e. pH 5.0: pH 6.0 and pH 6.7 did not affect the soluble nitrogen production significantly.